Effect of CYP2C9 on the migration, invasion and proliferation of hepatocellular carcinoma cells - ZHANG Tuo; LI Dajun; WANG Haitao; ZHANG Peng (Yixue xinzhi zazhi)
Objective To explore whether CYP2C9 is involved in the occurrence and development of hepatocellular carcinoma (HCC) and its function in the migration, invasion and proliferation of HCC cells.Methods The transcriptome data of HCC were retrieved from the TCGA database to analyze the expression of CYP2C9 and role of CYP2C9 in the prognosis of HCC; Constructing stable CYP2C9 overexpression cell lines of HepG2 and MHCC97H, detecting the effects of CYP2C9 overexpression on the migration, invasion and epithelial mesenchymal transition (EMT) process of HCC cells through Transwell migration assay, Transwell invasion assay, and Western Blot assay, respectively; The effect of CYP2C9 overexpression on the proliferation ability of HCC cells was detected through CCK-8 assay, colony formation assay, and Western Blot assay.Results Bioinformatics analysis showed that the expression of CYP2C9 was significantly downregulated in HCC , and the expression of CYP2C9 was positively correlated with the clinical prognosis of HCC patients; The results of cellular and molecular experiments showed that CYP2C9 overexpression significantly inhibited the migration, invasion and EMT process of HepG2 and MHCC97H cells, whereas had no significant effect on cell proliferation.Conclusion CYP2C9 may affect the progression of HCC by inhibiting the migration, invasion, and EMT processes of HCC cells.